2009
DOI: 10.2147/vhrm.s5798
|View full text |Cite
|
Sign up to set email alerts
|

Hematocrit and mean arterial blood pressure in pre- and postmenopause women

Abstract: The relationship between mean arterial blood pressure (MAP) and hematocrit (Hct) was studied in pre-and postmenopause women in the city of Durango, Mexico. Premenopause women show a negative trend between parameters that is not statistically significant. MAP and Hct are directly related in postmenopause women (p  0.01). It is proposed that that this MAP/Hct relationship is in part due to differences in endothelial function where menopause decreases the capacity of the endothelium to respond to increased blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…In a study of 128 normotensive members of a large employed population in New York City (51 ± 10 years) there was a significant independent relation between MAP and blood viscosity, 9 and a study of 628 individuals in the population of Victoria de Durango with men and women pooled data showed a weak positive correlation between MAP and Hct. 10 Our findings and some 11 , 12 but not all results in the literature 13 , 14 support the contention that Hct and blood viscosity are not a factor in regulating blood pressure in the healthy normal population within limits that include the systematic elevation of Hct due to adaptation to moderate altitude.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In a study of 128 normotensive members of a large employed population in New York City (51 ± 10 years) there was a significant independent relation between MAP and blood viscosity, 9 and a study of 628 individuals in the population of Victoria de Durango with men and women pooled data showed a weak positive correlation between MAP and Hct. 10 Our findings and some 11 , 12 but not all results in the literature 13 , 14 support the contention that Hct and blood viscosity are not a factor in regulating blood pressure in the healthy normal population within limits that include the systematic elevation of Hct due to adaptation to moderate altitude.…”
Section: Discussionsupporting
confidence: 75%
“…The results of this study, those from experimental studies 16 and results in children 12 and premenopausal women 11 indicate that blood pressure is not correlated with blood viscosity. Therefore a population presenting a positive correlation between blood pressure and blood viscosity (or Hct) is probably affected by endothelial dysfunction and/or pathologies that reduce or abolish the endothelial response to shear stress.…”
Section: Discussionmentioning
confidence: 43%
“…The effect of aging on endothelial function is evident in women that pass from pre- to postmenopause. 31 Salazar Vázquez et al 32 analyzed the distribution of MAP and Hct in a population of pre- and postmenopause women from the city of Durango, Mexico. In this study, healthy nonsmoking premenopausal women ( n =85) showed a nonsignificant negative correlation ( P =0.5) between MAP and Hct, while menopausal women ( n =92) presented a positive correlation ( P <0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Women aged >60 years in the city of Stockholm, Sweden, ( n =2,189) showed an identical MAP/Hct trend to that of menopausal women in Durango. 32 …”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Several studies report the association of conditions such as mean arterial blood pressure increase and osteoporosis with increased hematocrit in the postmenopausal period and therefore an increase in blood viscosity. 20,21 However, no studies have investigated the relationship between WBV or plasma viscosity and selected postmenopausal symptoms using the MRS. Demonstrating the existence of such a relationship may help in improving the quality of life of women in the postmenopausal period.…”
mentioning
confidence: 99%